2009
DOI: 10.1111/j.1365-2230.2008.03096.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of silicone gel in the treatment of fresh surgical scars: a randomized study

Abstract: The results of this study indicate that silicone gel is able to reduce the formation of keloid and hypertrophic scars and the signs/symptoms associated with the healing process (paraesthesia, pulling sensation, alterations in colour).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 11 publications
0
42
0
2
Order By: Relevance
“…79 Other measures, such as wearing a supportive bra or body corset, can additionally reduce the risk of KD located in the upper trunk or the midsternal region. The use of silicone as a prophylactic tool has been studied extensively 28,[80][81][82][83] and, with the exception of a study by Niessen et al, 83 the results so far have been favourable. 84 Topical steroid tape has also been shown to be effective in preventing recurrence, but has the potential for poor compliance as it is reliant on its continued application by the patient.…”
Section: Surgical Excision and Adjuvant Therapymentioning
confidence: 99%
“…79 Other measures, such as wearing a supportive bra or body corset, can additionally reduce the risk of KD located in the upper trunk or the midsternal region. The use of silicone as a prophylactic tool has been studied extensively 28,[80][81][82][83] and, with the exception of a study by Niessen et al, 83 the results so far have been favourable. 84 Topical steroid tape has also been shown to be effective in preventing recurrence, but has the potential for poor compliance as it is reliant on its continued application by the patient.…”
Section: Surgical Excision and Adjuvant Therapymentioning
confidence: 99%
“…The most common are the adverse effects of skin maceration and skin eruption, which have been reported in multiple studies. [75][76][77] All adverse effects resolved after discontinuing therapy without any adverse sequelae.…”
Section: Silicone Gelmentioning
confidence: 97%
“…In the treatment group, only 18 patients (27%) had formation of a nonphysiologic scar compared with the control group, where 25 patients (55%) had an altered scar. 75 Li-Tsang et al 76 evaluated the effects of silicone gel dressing and pressure therapy on posttraumatic hypertrophic scars. After 6 months of intervention, they concluded that SGS was more effective in alleviating pain and pruritus rather than scar thickness.…”
Section: Silicone Gelmentioning
confidence: 99%
See 1 more Smart Citation
“…Eng verknüpft mit den Prinzipien der Dehnung kommt der Narbenbehandlung eine besondere Bedeutung zu -zumal in der reparativen Phase der Wundheilung und Reifung einer Narbe bewegungseinschränkendes und limitierendes Gewebe mit funktionellen Einbußen einhergeht [5,11].…”
Section: Narbenbehandlungunclassified